Partisipasi Masyarakat dan Pengaruhnya Terhadap Proses Legislasi di Indonesia: Tinjauan Analitis Terhadap Peran Rakyat dalam Pembentukan Kebijakan Publik - Danar Aji Kirana; Muhammad Anas Ulil Abshor Munif; Mokhamad Fajar Zihady Faturrahman; Radithya Fathan Al Gibran (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2024)
As a state of law, legislation is fundamentally important for the way of life of a state. Legislation is made not only to regulate the powers that exist towards the ruler and the people, but also has important points in running the life of the state in accordance with what is to be realized in the constitution. Legislation basically has binding force on the entire public, so the public should be involved in the legislative process because this is also to encourage the quality of legal products that are in accordance with developments and public needs. Public participation is one of the important foundations in making legal products that favor and provide benefits to the community. Thus, this paper addresses how a legal product is made in accordance with public needs and how legislation should be implemented by the authorities. This study also discusses how to form recommendations regarding improving the quality of public participation in the legislative process.